Contemporary Management of Jugular Paraganglioma (Springer International Publishing, 2018)
This text serves as a useful resource for physicians managing jugular paragangliomas;the most common tumors of the jugular foramen. It reviews the challenges often faced in the management of these tumors due to the close proximity to critical adjacent structures including the dura, major vasculature, otic capsule and coursing cranial nerves. More conservative treatment options such as single fraction or fractionated stereotactic radiotherapy, subtotal tumor resection, and conservative observation that minimize morbidity and improve patient function and quality of life is also covered. Contemporary Management of Jugular Paraganglioma provides a concise yet comprehensive overview of the current status of the field that will help guide otolaryngologists, neurosurgeons, facial plastic surgeons, speech pathologists and residents involved in the care of patients with jugular paraganglioma.